Kafka body artist. Psychosomantics of a fasting artist - Bottacin Cantoni, Lorenza (Scenari, 2021)
The essay analyzes the act of writing in Kafka in order to show that writing is not simply the production of a literary work of art. Writing represents, for Kafka, a way to perform and it involves both the mind and the body of the artist. Body is a pivotal notion in Kafka’s novels and tales, but it is also the center of many letters and notes in his diaries, which often focus on psycho-somatic and physical details. Writing itself emerges as a physiological need for Kafka, who dedicates all his energies to the act of writing. The author’s life develops in a ceaseless tension to write; literature becomes an all-encompassing instance. Thus, it is possible to read Kafka’s life as a bios graphikos (writing-life) which is not simply an autobiography, but it is an integral, all-embracing performance. This way of living requires physical exercise, practices of askesis, it stikes and transforms the body from the inside. Therefore it is possible to read the switch from the first person to the third person (Er) as the extreme effort to bring together life and writing, body and art, an attempt that, however, leads to the death of the iand to the full (even physical) annihilation of the author, as exemplified in the tale A Hunger Artist.